Substituting Fish Meal with Tubiechong (Eupolyphaga sinensis) By-Product in the Diets of Largemouth Bass (Micropterus salmoides): Effects on Growth, Meat Quality, and Liver Health - Yuhua Yue; Binbin Tong; Mingshi Chen; Xiaoxue Bao; Yanming Qiu; Ying Yang; Hui Yu; Yingying Yu (Aquaculture Nutrition)
A feeding trial was conducted to evaluate the effect of replacing 0% (control), 10% (T10), 20% (T20), 30% (T30), and 40% (T40) fish meal with a Tubiechong (Eupolyphaga sinensis) by-product in largemouth bass (Micropterus salmoides). Triplicate groups of 30 fish (5.36±0.01 g) were fed two times daily to apparent satiation for 60 days. The experimental results showed that the Tubiechong by-product could improve the growth performance of largemouth bass by increasing the FBW, WGR, and SGR until the replacement ratio was 40%. The quadratic regression analysis showed that the proportion of the Tubiechong by-product was 20.79% and 20.91%, respectively, when WGR and SGR were the best. Concurrently, the meat quality in the replacement groups was higher, specifically, the lightness and white values were higher, and the water loss rates were lower (P<0.05) than that in the control group. Moreover, the changes of the activities of CAT and GSH in the liver and T-AOC and GSH in serum could reveal the antioxidant capacity improvement of fish by the Tubiechong by-product. In the study, the replacement groups had lower T-CHO and HDL-C in serum (P<0.05), indicating that the Tubiechong by-product had an active role in improving blood lipid and regulating lipid metabolism. Simultaneously, the replacement groups had a normal structure with central hepatocytes’ nuclei and deviated from the center partly, while most of the hepatocytes were swollen in the control group with nuclear degeneration. The results showed that the Tubiechong by-product had a positive effect on the liver health of fish. Conclusively, the present study indicated that the partial dietary replacement of fish meal using the Tubiechong by-product (for up to 40% replacement level) in the diet of largemouth bass not only caused no adverse effects on fish health but also improved the growth performance, meat quality, antioxidant capacity, and hepatic health and is conducive to supplying nutritious, high-quality, and healthy aquatic products.